SOSIALISASI PENGENALAN ANAK TUNAGRAHITA PADA MIN 07 SELUMA - Oci Mulia Sari; Azizah Munawaroh; Yusti Asmeri; Piki Apsir Pratama; Nova Asvio (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Children with mental retardation (mental retardation) are children who experience disorders of psychological development and intelligence abilities so that they have an impact on cognitive development and adaptive attitudes, so that there are differences in children in general. this affects the level of mentally retarded children, namely starting from the early stages of the mild, moderate, severe and very heavy categories. It is very important to realize this from all component parties, including children and the surrounding community. However, in reality there is still very low understanding of mentally retarded children among children and society. Based on these problems, it is necessary to socialize efforts about mentally retarded children (mental retardation). This activity was carried out at the community service center, namely at MIN 07 Seluma, Serambi Gunung Village, Kec. Talo, Kab. Seluma. With an explanation of the meaning of mentally retarded children or mental retardation. The method used in this service is socialization with the target students of MIN 07 Seluma with the method of question and answer activities and lectures. Based on the results of the initial survey, there are still many students who do not know about mentally retarded children. This service activity was carried out in April 2023 at MIN 07 Seluma.